QSAR Studies on 3-Iodo-4-phenoxypyridinone Series Against HIV-1 Activity - Mishra, Saloni; Mishra, J.P. (Asian Journal of Chemistry, 2010)
The QSAR studies have been carried out on a set of 27 molecules of 3-iodo-4-phenoxypyridinone series which were reported as inhibitor of HIV-1. The present study was undertaken to identify the important physico chemical parameters that affect the antiviral (anti HIV-1 activity) of the given series of drug molecules. The best QSAR model thus obtained, have high statistical significance (> 99.9 %) and moderate correlation coefficient (r = 0.795) led us to know that molar refractivity and resonance are showing negative effect on the pyridinone moiety, whereas the field effect is positively influencing the moiety. As there is only one substituent one can see the steric effect is negative for the result.